Validation of the FAINT risk score in a large prospective international multicenter study. (25th November 2020) - Du Fay De Lavallaz, J; Zimmermann, T; Badertscher, P; Flores, D; Widmer, V; Walter, J; Belkin, M; Boeddinghaus, J; Nestelberger, T; Reichlin, T; Kuehne, M; Christ, M; et al.
Abstract: Background: Risk stratification of older patients presenting to the Emergency Department (ED) with syncope remains an unmet clinical need. The FAINT Score was derived in a large American cohort in an attempt to predict 30-day serious cardiac outcomes in patients >60y.o. While a FAINT score of 0 showed high sensitivity to exclude death and serious outcomes at 30 days in the derivation cohort, it remains unvalidated. Methods: We validated the FAINT score (History of heart failure, history of arrhythmia, initial ECG result abnormal, elevate NT-proBNP, elevated hs-troponin T) in a large prospective international multicenter study recruiting patients 40 years presenting to the ED with syncope within the last 12 hours in eight countries on three continents. Main outcome measure was 30-day serious cardiac events or mortality. We assessed the performance and calibration of the FAINT score for validation and compared it to the OESIL score (Age >64y, cardiovascular disease history, syncope without prodromes, abnormal ECG). Results: 1885 patients were eligible for this validation analysis. 169 (8.9%) patients experienced 30-day serious adverse events. A FAINT score of 0 was present for 378 patients (20% of the cohort) and allowed for a sensitivity of 0.97 to rule out adverse events and death at 30-days. A FAINT score of 0 or 1 was present for 626 patients (33% of the cohort) and allowed for a sensitivity of 0.92. The area under the receiver operating characteristic curve (AUC) for the FAINT score was 0.75 (95%, Confidence Interval (CI) 0.72–0.79), which was comparable to the performance of N-terminal pro-B-type natriuretic peptide (NT-proBNP) or high-sensitivity Troponin T (hs-cTnT) alone, which are two biomarkers used in the FAINT score. The score did not outperform the OESIL score. A calibration curve showed that the score was extremely well calibrated for low-risk patients. Conclusion: This is the first validation of the FAINT score in a large international syncope cohort. The safety of a FAINT score of 0 or 1 was good and comparable to the results obtained in the derivation cohort. While the score is suitable to highlight low-risk patients and calibrates well in an external cohort, its discrimination for higher risk patients is not better than biomarkers alone or an older, less complex risk score. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): University Hospital Basel, Switzerland